DIFFERENT ROUTES FOR THE SYNTHESIS OF BENZALDEHYDE-BASED DIHYDROPYIMIDINONES VIA BIGINELLI REACTION - Ilfahmi, Yan Alamanda; Fadlan, Arif (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2023)
Multicomponent reactions involving three or more reactants are commonly used to prepare dihydropyrimidinone with various bioactivities. This study reports the different routes for the synthesis of benzaldehyde-based dihydropyrimidinone via the Biginelli reaction and investigates the yield of the obtained products. The synthesis was performed via routes A, B, C, D, and E based on the formation of iminium, enamine, and Knoevenagel intermediates between urea, benzaldehyde, and ethyl acetoacetate. Route A, through a one-pot reaction via iminium, produced dihydropyrimidinone with a yield of 58%. The product from route B via iminium was obtained in 62% yield. Route C and D occurred via enamine at room temperature, and reflux gave the product 31% and 40% yield, respectively. Route E involving Knoevenagel intermediate provided the product in a 38% yield. 1H NMR, FTIR, and MS spectroscopic techniques were used for structure elucidation.